The Association between Menstrual Disorder and Work Disturbance among Employees - Laila Nuranna; Iftikar Abdullah; I. Putu G. Kayika; Gita Pratama (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To investigate the association between menstrualdisorders including each menstrual cycle disorder, durationand volume of menstrual bleeding disorder, menstrual intervaldisorder, and another disorder that related to menstruationagainst disruption of work among employees.Methods: This study used a cross sectional design. Samplerandomization with winpepi® software for Windows 7®. Dataanalysis using SPSS 24® software for Windows 7®.Results: A total of 150 subjects were recruited in this study. Theprevalence of menstrual disorder was 87%, menstrual cycledisorder 3%. Menstrual volume disorder 31%, 15% menstrualabnormalities, 83% menstrual pain disorder and premenstrualsyndrome 71%. Prevalence of work disturbance was 49% formild disturbance, 47% for moderate disturbance and severework disturbance by 4%. There was a relationship betweenmenstrual volume disorder, hypermenorrhoea, and menstrual /dysmenorrhoea pain to occupational disruption among theemployee at RSCM (p <0.001). The submission of the proposedleaves due to menstrual disorder in the proposed permit for1 day by 73%.Conclusion: The prevalence of severe work disturbance due tomenstruation is not high but can lead to disruption in runningjobs and activities. However, it is important to be a concern so thatthe employees get good management and care.Keywords: employee, menstrual leave, menstrual disorder, prevalence,work disturbance